2006
DOI: 10.1530/rep.1.00916
|View full text |Cite
|
Sign up to set email alerts
|

Graft site and gonadotrophin stimulation influences the number and quality of oocytes from murine ovarian tissue grafts

Abstract: Ovarian tissue cryopreservation and subsequent transplantation can restore fertility in cancer patients. This study used a mouse ovarian grafting model to investigate whether the graft site (bursal cavity, the kidney capsule or subcutaneous) influences the number, fertilization rate and developmental potential of oocytes recovered from grafts and whether using a standard gonadotrophin stimulation protocol would increase oocyte yield from the grafts. Mouse ovarian tissue was grafted into four week old mice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 60 publications
3
37
0
5
Order By: Relevance
“…Renal envelopes were highly preferred in the past, and the transplanted ovaries developed well there (Carroll et al 1990, Waterhouse et al 2004. In recent years, subcutaneous and muscle tissues have become the alternative sites for ovary implants (Oktay et al 2003, Lee et al 2004, Yang et al 2006, Schubert et al 2008, Soleimani et al 2008, Eimani et al 2009). Ovarian transplantation under the kidney capsule requires a more difficult surgical operation, and the development of grafts cannot be observed during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Renal envelopes were highly preferred in the past, and the transplanted ovaries developed well there (Carroll et al 1990, Waterhouse et al 2004. In recent years, subcutaneous and muscle tissues have become the alternative sites for ovary implants (Oktay et al 2003, Lee et al 2004, Yang et al 2006, Schubert et al 2008, Soleimani et al 2008, Eimani et al 2009). Ovarian transplantation under the kidney capsule requires a more difficult surgical operation, and the development of grafts cannot be observed during the process.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were few good quality embryos, and successful pregnancy did not occur. In mice, graft survival was poorer and the number of oocytes retrieved was lower from subcutaneous compared with other graft sites [18]. Cryopreserved ovarian tissues are subject to freezing, thawing, and ischemic injury throughout the transplantation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Hernandez-Fonseca et al [38] showed that human ovarian cortical grafts transplanted under the KC had significantly higher proportions of growing follicles compared with those recovered from the SC. Furthermore, Yang et al [39] showed that graft recovery rate and oocyte yield were significantly less at the SC graft site with only 56-58% of the grafts recovered compared with the OB and KC which had 98-100% and 93-95% of the grafts retrieved, respectively. The number of two-cell embryos produced was significantly higher with oocytes from grafts to the OB, compared with KC and SC graft sites [39].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yang et al [39] showed that graft recovery rate and oocyte yield were significantly less at the SC graft site with only 56-58% of the grafts recovered compared with the OB and KC which had 98-100% and 93-95% of the grafts retrieved, respectively. The number of two-cell embryos produced was significantly higher with oocytes from grafts to the OB, compared with KC and SC graft sites [39]. Our present study also showed that the effect of gonadotrophins on follicular development after xenografting was influenced by the site of transplantation.…”
Section: Discussionmentioning
confidence: 99%